Data assisted-modeling of the liver organ on a chip dynamics - Smith, Connor (Kansas State University, 2022)
The concept of mathematical modeling to develop a digital twin of biological processes is in a nascent state. Despite the limited understanding of many biological pathways, a well-trained mathematical model can successfully conduct many experiments to guide development more efficiently. The Organ On a Chip (OOC) concept is a feat of engineering and biology where organs can be simulated in vitro for drug discovery, toxicology, and pharmacokinetic/pharmacodynamic (PK/PD) studies. My Master’s Report aims to conduct a literature review on OOCs and the kinetics of the biological pathways in the liver related to Non-alcoholic Fatty Liver Disease (NAFLD). The findings will be applied to develop a data-assisted mathematical modeling framework. A liver OOC for NAFLD is used as the base model where the kinetics of the reactions of metabolites, substrates, and drugs are simulated. A hybrid modeling approach combining first-principle-based models, PK/PD, and machine learning will enable a better understanding of factors impacting NAFLD.
Keywords: Mathematical modeling; Organ on a chip